PENGARUH PERENCANAAN PAJAK DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN SUB SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2024 - Azzahra, Maya; Khodijah, Ina; Komarudin, Mochamad Fahru (Yayasan Education and Social Center, 2025)
The purpose of this study is to determine whether there is an influence of the role of taxes and profitability on the value of banking sector companies listed on the Indonesian Stock Exchange in 2020-2024. The research method used is associative quantitative. The study population includes all banking subsector companies listed on the IDX. The research sample was selected using a purposive sampling technique with certain criteria, resulting in a number of companies that are consistent in publishing annual financial reports throughout the observation period. Data were analyzed using multiple regression tests. The results of the hypothesis testing show that: (1) Tax planning has a positive effect on company value, as evidenced by the t-value of 15.818 which is greater than the t-table of 2.145, and a significance value of 0.000 <0.05. (2) Profitability also has a negative effect on company value, as indicated by the t-value of -4.156 which is smaller than the t-table of -2.145, with a significance value of 0.000 <0.05. (3) Simultaneously, tax planning and profitability together have a significant influence on company value, as evidenced by the calculated F value of 288.786, which is much greater than the F table of 3.739.